Antibiotic use and resistance in Belgium: the impact of two decades of multi-faceted campaigning. Issue 4 (4th July 2021) - Bruyndonckx, R.; Coenen, S.; Hens, N.; Vandael, E.; Catry, B.; Goossens, H.
ABSTRACT: Objective : To present an overview of almost two decades of multi-faceted campaigning by the Belgian Antibiotic Policy Coordination Committee (BAPCOC) and partners, and its impact on public and prescribers' awareness, outpatient antibiotic use, its cost and antimicrobial resistance in Belgium.Methods : Awareness of both public and prescribers was assessed through pre- and post-campaign interviews and surveys. Outpatient antibiotic use was evaluated using national reimbursement data expressed in number of defined daily doses and packages (a good proxy for treatments) per 1000 inhabitants per day (DID and PID, respectively) from July 1997 to June 2018. Its cost was studied using the same data expressed in number of euros per 1000 inhabitants per day. Antimicrobial resistance was evaluated between 1986 and 2017 using national data on the proportion of Streptococcus pneumoniae isolates not susceptible to penicillins, macrolides and tetracyclines.Results : Antibiotic awareness improved significantly, with general practitioners preferred by 87.5% of respondents as source of information. The Belgian outpatient antibiotic use has decreased by 12.8% in DID and by 42.8% in PID in the 2017-2018 winter compared to the winter before the start of its public awareness campaigns (1999-2000). This evolution coincided with decreasing costs for antibiotics and decreasing antimicrobial resistance. Despite multi-faceted campaigning, outpatient antibiotic use and use of broad-spectrum antibiotics, especially fluoroquinolones and amoxicillin with clavulanic acid, are still high in Belgium.Conclusion : Almost two decades of multi-faceted campaigning coincide with improvements in antibiotic awareness among the public and prescribers, outpatient antibiotic use and resistance. Nevertheless, additional efforts are needed to reach the targets set in BAPCOC's national action plan 2014-2019. Therefore, a new national action plan was developed for 2020-2024 using a One Health approach.